PROBLEM SOLVING OF NON-EQUIVALENCE PROBLEMS IN ENGLISH INTO INDONESIAN TEXT - Widhiya Ninsiana (Jurnal Pedagogy, 2016)
In the process of transferring one message of Source Language (SL) to Target Language (TL) in a translation must be careful by a translator, because one word may have more than one meaning. By knowing the possible meanings of a word, the meanings appropriately should be translated by a translator, and the readers will get the meaning and information of the target text. The equal meaning of source language to the target language is equivalnce, but non-equivalence occurs when the meaning in source language is not translated into the target language. There are many strategies to solve the problems of non-equivalence in Indonesian into English. A translator has a strategy to solve it. These strategies, that is, cultural, loan word, pharaphase, omission, semantically, hyponyms, etc.